A comparative analysis of energy use and CO2 emissions in the manufacturing and service industries of Sweden (2013)
This study analyses the trends in energy use and CO2 emissions in the manufacturing industry and service sector. Using data at the two-digit aggregation level for the Swedish manufacturing and service industries, this empirical study intends to examine energy use, energy efficiency and CO 2 emissions using data envelopment analysis (DEA) and panel data techniques. DEA is applied to assess energy efficiency within a production framework. Panel data techniques are used to determine which variables influence energy efficiency. The results from the DEA reveal significant variations in energy efficiency across the manufacturing and service industries. The results for these sectors also indicate that technical efficiency and energy efficiency have increased while CO2 emissions have decreased, especially in recent years. The results of the panel data techniques demonstrate that increased energy taxes, electricity consumption, investments and labour productivity generate higher energy efficiency, while higher fossil fuel consumption leads to lower energy efficiency. All of the findings of this study are important for developing effective energy policies that encourage better energy use and management in the industrial sector. Copyright © 2013 Inderscience Enterprises Ltd.